Study of Anisotropy Characteristics of Bogor Volcanic Soil - Yusi Sulastri; Paulus Pramono Rahardjo (Kadiri University, 2021)
Anisotropy in soil results from the deposition process which describes the characteristics of the soil grains or is caused by stress or from the consequences of stresses caused during deposition and subsequent erosion. All soils behave in general anisotropy and some exhibit undrained shear strength. This study conducted 2 tests, namely the first field testing with original soil samples in the form of CPTu and dilatometer. The CPTu test's objective is to determine the vertical soil parameters, while the dilatometer is to determine the horizontal soil parameters. This study indicates that the indication of anisotropy in all shear strength tests is evident in the results of the CPTu test and the Dilatometer test. TX - UU and consolidation show that the horizontal shear strength (Suh) is greater than the vertical slope shear strength (Suv). In this case, the ratio obtained for shear strength is Suh = 1.3 Suv. And from the results of the consolidation test in the laboratory, it was found that the horizontal compression index parameterÂ (Cc horizontal)Â was greater than the vertical (Cc vertical) and the horizontal coefficient of consolidation (Ch) is greater than the vertical coefficient of consolidation (Cv).